2015
DOI: 10.1111/jop.12351
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐155‐5p is associated with oral squamous cell carcinoma metastasis and poor prognosis

Abstract: Background Abnormal miRNA expression was recently implicated in the metastasis of oral squamous cell carcinoma (OSCC) and with a poor prognosis. The initiation of the invasion‐metastasis cascade involves epithelial‐mesenchymal transition (EMT). Our aim was to clarify how miRNA, especially miR‐155‐5p misexpression contributes to OSCC metastasis through EMT. Methods We collected tumor samples from 73 subjects with OSCC. The samples were analyzed by quantitative reverse‐transcription polymerase chain reaction (qR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 26 publications
3
56
1
Order By: Relevance
“…Baba et al [22] confirmed that microRNA-155-5p is upregulated in oral squamous cell carcinoma and is correlated with tumor malignancy. It promotes epithelial mesenchymal transformation (EMT) by increasing SOCS1 and decreasing STAT3 expressions, which in turn promote tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Baba et al [22] confirmed that microRNA-155-5p is upregulated in oral squamous cell carcinoma and is correlated with tumor malignancy. It promotes epithelial mesenchymal transformation (EMT) by increasing SOCS1 and decreasing STAT3 expressions, which in turn promote tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…16,24,69,81,82 Interestingly, Lerner et al and Scapoli et al found hsa-mir-155-5p to be downregulated in HNSCC and OSCC tissue. OS of oral squamous cell carcinoma was analyzed using Kaplan-Meier method.…”
Section: Hsa-mir-143-3pmentioning
confidence: 99%
“…OS of oral squamous cell carcinoma was analyzed using Kaplan-Meier method. 15,16,24,85 Furthermore, Rather et al have demonstrated that hsa-mir-155-5p overexpression is related to larger OSCC in a mouse model. HRs were calculated using a univariate cox regression hazard model, and P values were calculated using a log-rank test.…”
Section: Hsa-mir-143-3pmentioning
confidence: 99%
See 2 more Smart Citations